Algerian experience in the management of the judicial archive - ben chahida, mohamed (Journal of Social Sciences and Humanities, 2020)
The preservation of judicial records is one of the most important challenges currently facing the Department of Justice for a number of reasons, the most important of which is the massive accumulation of funds since independence,With this challenge, the Ministry of Justice was forced to review some of the regulatory texts that did not abound in its meaning, hence the importance of regulatory texts, laws and executive decrees that can hoist the level of management of the various bodies of the legal sector since they are the essential pillars in the management process, and also raise the level of the people in charge of this work, we note through this study that the regulatory texts relating to the judicial archives are few compared to the regulatory texts in the field of administrative archives, not to mention that they are not used in the services concerned by the management of this type of archives in the depots which are imparted to them. This documentary production has become a turning point if we do not say the stumbling block in the management, so we should find the effective way to govern this increase, and therefore the Algerian state has given the archive sector of great importance and established this importance with legal texts to increase it more official and serious considering the archive reference The archive forms the cistern in which the identity of the society is right and involves, under its banner, the lines of nations and peoples towards building a future of objective logic on the pride of children. In general, the number of texts issued in the field of archives and publications in the Official Gazette since 1962 to March 2005 amounted to about sixty-five (65) texts were distributed among orders, laws, decrees, and decisions, in addition to a large number of leaflets and instructions